Comparison of two anti-diabetic monoestolides regarding effects on intact murine liver tissue - Rychtrmoc, David; Staňková, Pavla; Kučera, Otto; Červinková, Zuzana (Archives of physiology and biochemistry, 2022)
CONTEXT: Monoestolides belonging to the fatty acid-hydroxy fatty acid (FAHFA) family have recently emerged as promising insulin sensitizers. OBJECTIVE: To investigate and compare impact of two selected FAHFA isomers, namely 9-hexadecanoyloxy-octadecanoic acid [9-PAHSA] and 9-(9Z-octadecenoyloxy)-octadecanoic acid [9-OAHSA], on intact livers in C57BL/6J mice. MATERIALS AND METHODS: Short-term in vivo study with intragastric gavage of 13 mg/kg of substances. Morphological, biochemical and high-resolution respirometric assessment of plasma and liver tissue or homogenates thereof. RESULTS: The 9-OAHSA-gavaged mice had the highest final total body weight, the lowest free fatty acid circulating levels and the highest plasma activities of both ALT and AST. No significant changes of ambient glycaemia were found, however 9-PAHSA-gavaged mice tended to have lower glycaemia than other animals. Respirometry proved no substance-dependent differences. DISCUSSION AND CONCLUSION: 9-PAHSA was more metabolically beneficial and less hepatotoxic than 9-OAHSA. Bioenergetic machinery of liver homogenates seemed unaffected at our FAHFA dose.
Keywords: Mice; játra; myši inbrední C57BL; Animals; mastné kyseliny; Liver; Insulin; zvířata; Mice, Inbred C57BL; myši; Fatty Acids; inzulin